Reducing respiration rate and increasing chemical stability of mulberry fruits by using postharvest putrescine and melatonin - Şadiye Peral Eyduran; Ayşen Melda Çolak; Selma Kuru Berk; Mustafa Sakaldaş; Fatih Şen; Muttalip Gundogdu (BMC Plant Biology)
Abstract Background Plant growth regulators have been widely used to extend the cold storage period of fruits and preserve quality. These phytohormones help mulberry fruit in maintaining its postharvest quality and soft texture, prevent from spoiling during cold. For this purpose, mulberry fruit were stored in cold for 5, 10 and 15 day (0.5 °C and 90% RH) and the impacts of melatonin (1.0 mM) and putrescine (1.0 mM) on quality parameters, phenolic compounds (gallic, protocatechuic, catechin, syringic, p-coumaric, chlorogenic, o-coumaric, ferulic, phloridzin, rutin and quercetin) and organic acids (malic, citric, succinic, oxalic, tartaric, fumaric and ascorbic) were investigated. Results The combined application of putrescine and melatonin maintained the weight loss (4.35%), decay rate (9.48%) and 29.89% lower respiration rate (6.07 mg CO2 kg− 1 h− 1) in mulberry fruits stored for 15 d as compared to the control. Phenolic compounds (especially rutin) and organic acids were found to be more affected by melatonin and putrescine applications compared to other findings in this study. However, melatonin treatment is more effective in maintaining the level of organic acids and phenolic compounds in mulberry fruit during storage than the putrescine. It was determined that soluble solids content, weight loss, decay rate and pH values had a positive relationship with each other. Also, it was also seen that phenolic compounds and organic acids had a linear relationship. Conclusion The combined application of melatonin and putrescine was found more effective in maintaining the quality parameters of mulberry fruits during cold storage.